A review of legalisation of illegal factories program: case study of Selangor, Malaysia - Mohd Daniar, Nurul Ain; Bachok, Syahriah; Mohamed Osman, Mariana; Abdullah, Muhammad Faris (2016)
Selangor, one of the developed state in Malaysia has experienced enormous financial losses regarding land premiums and other taxes due to the existence of illegal factories existed before 2006. Besides financial losses to the state, the activity of these illegal factories also creates problems to the surrounding communities, especially in terms of environmental pollution and incompatible land uses. The Selangor state government has initiated a legalisation program in which the owners were given incentives to apply for approvals to legalise their factories. However, the participation of the owners was poor because half of them did not apply for planning approval and building plan. Thus, this paper attempts to discuss the current scenario of illegal factories in Selangor and the program created by the Selangor state to tackle the issue. The method adopted is through literature reviews and content analysis by collecting secondary data such as report and policy papers from the local and state authority, as well published newspapers. It is hoped that this paper can be useful for future references towards implementing legalisation effort of illegal factories.